Is a More Comprehensive Surgery Necessary in Patients With Uterine Serous Carcinoma?. Issue 7 (1st September 2015) - Touhami, Omar; Trinh, Xuan-Bich; Gregoire, Jean; Sebastianelli, Alexandra; Renaud, Marie-Claude; Grondin, Katherine; Plante, Marie
Abstract : Objective: Uterine serous carcinoma (USC) is an aggressive histologic subtype of endometrial cancer that shares similarities to serous ovarian cancer, with a propensity for spread to the upper abdomen, a high recurrence rate, and a poor prognosis. The aim of this study was to determine whether the traditional surgical staging procedure for endometrial cancer was adequate for USC or whether a more extensive surgery, similar to the staging procedure for ovarian cancer, needs to be performed. Specifically, the roles of omentectomy and sentinel lymph node (SLN) mapping were evaluated. Methods: We retrospectively identified cases of presumed clinical stage I USC at our institution from April 2005 to March 2014. Medical records were reviewed for the following information: age at diagnosis, preoperative imaging, operative findings, surgical procedure, and final histology with definitive International Federation of Gynecology and Obstetrics stage. Results: A total of 39 patients with presumed clinical stage I USC were identified. According to the final pathology report, the surgical stage was as follows: 17 stage IA (44%), 8 stage IB (20%), 3 stage II (8%), 2 stage IIIA (5%), 6 stage IIIC1 (15%), 1 IIIC2 (3%), and 2 stage IVB (5%). Therefore, 14 patients (36%) were surgically upstaged, but none of the patients had their clinical disease upstaged by virtue of finding microscopic metastatic disease in an otherwise normal-looking omentum. Sentinel lymph node mapping was performed in 19 patients (42%). Sensitivity and negative predictive value of SLN mapping were 100% when at least 1 SLN was identified. Conclusions: The detection of microscopic disease in radiologically and clinically normal-appearing omentum seems to be rare in USC. Sentinel lymph node mapping seems to be valuable in the serous subtype of endometrial cancer. A less extensive surgery may be possible in patients with USC as it seems to provide the same information as a more extensive surgery.